Social register locater. - Social Register Association (U.S.) (SR, 1907)
"The locater lists in alphabetical order every name in all the Social registers and indicates the family's head under which it may be found and the city in which the name appears."
"The locater lists in alphabetical order every name in all the Social registers and indicates the family's head under which it may be found and the city in which the name appears."
Also issued online.
The Social register is published with a winter issue for each city and a summer issue combined in one volume for all the cities.
Latest issue consulted: Vol. 68 (1976).
Keywords: Social registers / fast / (OCoLC)fst01122849; Social registers / United States / Indexes.; United States / fast / (OCoLC)fst01204155; United States / Directories; Periodicals / fast / (OCoLC)fst01411641; Directories / fast / (OCoLC)fst01423796